Synthesis of alumina from the Acid Solution AICl3 and Characterization by DRX - Muñoz H., Patricio (2001)
In order to use the alumina as a hydrogenation catalyst carrier, from AICl3 acid solutlon produced at the highpurity hydrogen generation to the laboratory level, aplying precipltation, filtration, whashlng and drying methods they were synthesized two types of products nominated as Alumina(I) and Alumina(II); these products were applied to the treatment of thermal transition phases and the obtained products were characterized by DRX. So, by calcinatlon for 5 h, they were obtained the following results: y-Al203 amorphous was formed from Alumina(I) at 500ºC, y-Al203 crystal structure with 0,9437 A size was produced at 11OOºC, x- Al20 3 was formad by Alumina(ll) calcination at 500ºC and 850ºC , a mixing of k-Al203 and a- Al20 3 phases were formed from Alumlna(II) at 1100ºC. On the other hand, calcinating by second time y-Al203 amorphous at 850 and 1100ºC far 5 h, they were formad y-Al203 crystal structures with 0,5542 A and 0,9437 A sizes respectively, and when x- Al203 was calclnated by second time at 600 and 850ºC the sama phase of x- Al20 3 was remained, but at 11OOºC were formad a mlxing of K-Al203 and a- Al20 3 phases. Flnally, the y-Al203 crystal structure produced without impurity could be used as a hydrogenation catalyst carrier.